Students’ satisfaction in using the IIUM Website - Abdul Kadir, Hasnah; Wok, Saodah (2018)
The 21st Century has witnessed tremendous development in Information Technology. With the development of the communication technology devices, the organisations including academic institutions are pressured to be accessible online. As an academic institution, the International Islamic University Malaysia (IIUM) is keeping abreast with the current technology. As such, this study aims to determine students’ satisfaction on using the IIUM website. Using the Uses and Gratification Theory (UGT), this study measures the relationships among the variables of satisfaction, awareness, perception, attitude, behaviour and usage of the IIUM website. The objectives of this study are to analyse the levels and relationships among the variables, besides determining the best predictor of satisfaction in using the IIUM website. A quantitative research design using the survey method with a self-administered questionnaire is used for data collection. A total of 409 students participated in this study. The results show that all the levels of tested variables: satisfaction, awareness, perception, attitude, behaviour and usage are positively related. Attitude is the best predictor for satisfaction in using the IIUM website. Students agree that the IIUM website is very useful for them through their college years. They rely on the website for their academic-related activities, course registration and downloading study materials online. Thus, the results support the UGT that focuses on user satisfaction. For suggestions, IIUM needs to regularly update the information on its website. The interface of the website needs to be attractive, simple and easy for users to search for academic-related information. Further, with the heavy usage of the smartphone among students, the website should have the mobile application to increase the users’ satisfaction level in using the IIUM website.